Microclimate Variations between Semienclosed and Open Sections of a Marathon Route. (7th October 2013) - Wong, Paulina; Lai, Poh-Chin; Hart, Melissa
Abstract : The Hong Kong Standard Chartered Marathon, held annually, is one of the most popular international marathon events. Its primarily urban environmental setting characterized by high-density urban areas, semienclosed tunnels, and suspension bridges, together with the herds of runners, has an influence on the microclimate along the marathon course. This study focused on assessing and comparing variations in temperature and vapour pressure (vis-à-vis relative humidity) against the crowd of runners, or the herd effects, in two different environmental settings along the marathon course: semienclosed (a tunnel) versus open space (a suspension bridge). A series of small iButtons were deployed at strategic locations along the course to undertake minute-by-minute measurements of temperature and relative humidity. It was found that herd effects of varying degrees were present in both semienclosed and open settings. Various environmental differences also played a role in ameliorating or amplifying the climatological effects of the herd of runners. Our study suggests that microclimate variations in different environmental settings and crowd conditions could have an impact on runners. This new knowledge can inform the design of marathon routes. It also establishes the feasibility of employing the iButton logging sensors for widespread deployment and monitoring of meteorological situations.